Analysis of Hospital Solid Waste Management in West Sumatra Province - Alhamda, Syukra; Herawati, Nova (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: The current situation in West Sumatra is that there are 1,899.15 tons of solid medical waste per year, including hazardous and toxic materials (B3), originating from 2,839 health facilities in West Sumatra, and hospitals or other health facilities are not allowed to dispose of medical waste carelessly, so it costs quite a lot. The poor management of this waste can be seen starting from the lack of efforts to prevent or at least reduce the amount of waste, the absence of a system for segregation, containerization, transportation, temporary storage, placement, or collection of waste that is not by regulations, and the inconsistent system for processing/final processing of waste and its disposalMethods: This qualitative research project will help us learn more about how hospitals in West Sumatra handle solid medical waste by looking at how they do it. The researcher is the crucial instrument; sampling data sources is done purposefully or snowballed, collection techniques are triangulation (combined), data analysis is inductive or qualitative, and the results of qualitative research emphasize meaning rather than generalization.Results: By researching 12 hospitals in West Sumatra, using interviews, researchers obtained information that there were other variables as hidden influences/other factors in this study, namely training in medical waste management and low levels of education for cleaning service personnel.